2005
DOI: 10.1093/ps/84.10.1604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-ketoglutarate on bone homeostasis and plasma amino acids in turkeys

Abstract: The objective of the study was to evaluate the effect of denervation and alpha-ketoglutarate (AKG) administration on the development of osteopenia in the turkey radius. At 22 d of age, all turkeys were subjected to neurectomy of the right radius. Control turkeys were given a saline solution into the crop each day for 97 d. Experimental turkeys were given 0.4 g of AKG/kg of BW into the crop each day. After 98 d, BW was not affected by the AKG treatment. Volumetric bone mineral density of the radius was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…The concentrations of all these amino acids were increased in our study in newborn piglets being under individual or combined prenatal influence of AKG [39]. Moreover, in 17-week old turkeys, plasma concentrations of proline and leucine were elevated by 53 % and 25 % after 14-week long oral administration with AKG at the same dosage as in the current study [24]. Available data from studies on growing turkeys have shown that 15-week administration with HMB increased concentration of cysteic acid, glutamine, valine, aspartate, glutamate, proline, alanine, isoleucine, leucine and phenylalanine, whilst body weights were not different in comparison to control birds [40].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The concentrations of all these amino acids were increased in our study in newborn piglets being under individual or combined prenatal influence of AKG [39]. Moreover, in 17-week old turkeys, plasma concentrations of proline and leucine were elevated by 53 % and 25 % after 14-week long oral administration with AKG at the same dosage as in the current study [24]. Available data from studies on growing turkeys have shown that 15-week administration with HMB increased concentration of cysteic acid, glutamine, valine, aspartate, glutamate, proline, alanine, isoleucine, leucine and phenylalanine, whilst body weights were not different in comparison to control birds [40].…”
Section: Discussionsupporting
confidence: 55%
“…In studies on growing turkeys, 14-week long administration with AKG eliminated neurectomy-induced osteopenia of radius increasing its weight, vBMD, A, Ix, MRWT, Wy and Wf. These advantageous effects were combined with higher serum concentration of proline and leucine in comparison to placebo-treated birds [24]. In other studies on sheep, two week long neonatal treatment with AKG improved Td, Cd and Wf of femur as well as increasing weight, length, Cd, Wy and the moments of maximum elastic strength and ultimate strength [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Such effects were Tatara et al Effects of total gastrectomy on plasma silicon and amino acid concentrations in men 1561 observed in studies on physiologically growing animals and in animals with developing osteopenia. 5,[20][21][22] In the current study, plasma concentration of alpha-amino-butyrate was shown to be significantly lower in the GX group of patients one year after the gastric surgery when compared to the control group. At this stage of the follow-up, plasma concentration of adipic acid was significantly higher in the gastrectomized group of patients when compared to both the baseline value and to the control group.…”
Section: Discussionsupporting
confidence: 46%
“…α ‐Ketoglutarate serves many functions in the organism. For example, it stimulates protein synthesis and inhibits protein degradation (Hammarqvist et al., 1991), functions as an ammonium ion scavenger via transformation to glutamate and increases plasma leucine and proline concentrations (Kristensen et al., 2002; Tatara et al., 2005a). Proline is the precursor of hydroxyproline, a qualitatively and quantitatively important amino acid in terms of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption is facilitated through secondary active transporters coupled to the sodium gradient known as the sodium dicarboxylate cotransporters (Pajor, 1999) with the highest rate of absorption in the small intestine followed by the stomach and colon (Buddington et al., 2004). Despite the low portal uptake of AKG and its short systemic half‐life (∼5 min) (Dabek et al., 2005), AKG increases bone mineral density and mechanical strength, when given orally to turkeys (Tatara et al., 2004, 2005a), pigs (Kowalik et al., 2005b) and lambs (Harrison et al., 2004; Tatara et al., 2007). Whilst the question of whether AKG supplements, given postnatally, have a permanent effect on bone mineralisation in pigs has yet to been resolved, a recent study has shown the potential usefulness of AKG treatment in preserving bone mass as well as lowering bone turnover in post‐menopausal women (Tocaj et al., 2003), results which suggest a link between enteral AKG and an increase in oestrogen levels.…”
Section: Introductionmentioning
confidence: 99%